PENGARUH MEDIA FILM ANIMASI TERHADAP KETERAMPILAN MENULIS PUISI DI SD - Pratika, Eka; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study was how the influence of the use of animated film media on the poetry writing skills of the fifth grade students on public elementary school 66 city Pontianak.This study aimed to determine the effect of the use of animated film media on students poetry writing skills. This study used an exsperimental method with a pre-exsperimental design of nonequivalent control group design. The population was all students from five classes totaling 65 people, while the sample was class 5A and class 5B which amounts to 65 people. Data collection techniques were measurement techniques, with data collection tools were written essays. Based on data analysis, the result of the average post-test experimental class= 75,52 and average post-test result of the control class= 67,88. This showed an increase in students in learning to write poetry using animated film media. After ttest was obtained tcount 2,674 for dk 54 and ?= 5% obtained ttable 2,006, which means tcount > ttable, then Ha is accepted, which means there is a significant influence on the use of animated film media. From the calculation of the effect size (ES), obtained (ES) of 0,8 with high criteria. Means the use of animated film media has a high influence on poetry writing skills.Key words : Animated Film Media, Influence, Poetry Writing Skills.